ANALYSIS OF THE INFLUENCE OF BRAND IMAGE, HALAL LABEL, AND CONSUMER REVIEWS OF PURCHASE DECISIONS WARDAH COSMETIC PRODUCTS - Nazwah Irawan, Sophie; Saputra, Fendi (International Journal of Business, Law, and Education, 2023)
The purpose of this study was to determine the significant effect on Brand Image, Halal Label, and Consumer Reviews on Purchase Decisions for Wardah Cosmetic Products. This research is a research using a quantitative approach. The population in this study are people who use Wardah Cosmetics in South Tangerang City. The sampling technique uses simple random sampling. The data analysis technique used in this study used SPSS software. Based on statistical tests, the results of the study show that Brand Image does not have a significant direct effect on purchasing decisions, Halal Labels do not directly have a significant effect on purchasing decisions, while Consumer Reviews have a significant effect on purchasing decisions.